Marine insurance fraud - Soyer, Baris (Milton Park, Abingdon, Oxon [UK]: Informa Law from Routledge, 2014)
'Helpfully split into 3 parts, this invaluable book provides a comprehensive and coherent legal analysis of the impact of fraud on marine insurance contracts.Part 1 analyses various market failings, which create a suitable environment for fraud. It is also intended in this part to consider the meaning of fraud from a legal perspective. Part 2 adopts a focused legal approach, and analyses the impact of fraud committed by parties to the insurance contract, i.e., assured, brokers and insurers. Part 3 examines the extent to which fraudulent activity is covered by standard marine policies, and deals with the fraudulent activity committed by third parties against the interest of the parties to the insurance contract.This book will be of huge assistance to practitioners specialising in marine insurance, as well as professionals, academics and students.'--
'This book provides a comprehensive and coherent legal analysis of the impact of fraud on the position of various parties to a marine insurance contract, as well as the cover provided by standard marine policies. The issues under discussion in this invaluable guide are also equally relevant in the context of non-marine insurance contracts. Helpfully divided into two parts, the first part deals with the impact of fraud committed by parties to the assured, brokers and insurers. The second part analyses the extent to which standard marine policies cover the fraudulent and dishonest activity of third parties to an insurance contract. This book will be of huge practical assistant to practitioners specialising in marine insurance as well as insurance generally, and to professionals, academics and post-graduate students'--
General overview of fraud in marine insurance -- Fraud committe by the assured at the outset -- Fraud committed by the assured at the post-contractual stage -- Fraund committed by the insurer -- Fraud committed by independent agents of the parties -- Potential impact of law reform -- Impact of fraud and other dishonest activity on insurance coverage.
Includes bibliographical references and index.
Keywords: Marine insurance -- Law and legislation -- United Kingdom -- Criminal provisions; Insurance crimes -- United Kingdom